Approaches and results of the applications of the classifications for patients with diabetic foot - Alicia Ascaño Ortega (Revista Cubana de Medicina Militar)
There is a large number of classification systems in patients with diabetic foot. The importance of a correct classification of injuries determines the treatment to be carried out and can provide data on the prognosis of patients regarding possible amputations. In recent years the trend is towards the development of more complex systems, with the use of technology. The McCook et al. classification has been the basis for the treatment of patients with diabetic foot in Cuba; To this, the hemodynamic classification was added later and when the Heberprot-p began to be applied, the Wagner classification was associated, but always with McCook's optics. This initial vision and its subsequent development have led Cuba to achieve minimal amputation figures, different from what happens in other countries. This work expresses the author's opinion about the results using the classifications used in Cuba.